La entrega de Medidas de Protección en Violencia Intrafamiliar como incide en el Principio Constitucional de Inocencia - Cueva Chacón, Diego Geovanny (2023)
Protection measures are the instrumental means by which the victim of domestic violence is protected; they are delivered through a judicial act with the judge's firm decision in favor of the victim and sanctioning the alleged aggressor. Although the measures have a protectionist purpose, they are sometimes used at the whim and whim of the victim, distancing the alleged aggressor from the family nucleus and the assets that are the means of economic support for the person and the family. From the constitutional level, it is imperative to analyze the delivery and use given to protection measures, their misuse or employment generates violation of constitutional and human rights, in this sense throughout this investigation it will be argued that it violates the constitutional principle of innocence, the constitutional mandate that states that every person is innocent until proven otherwise is broken; However, in the case of domestic violence, the person is treated as an aggressor and guilty; after being punished, he or she is allowed to resort to defense, without further meaning, given that he or she is outside and away from the home and its relatives. business. The procedural form in cases of domestic violence blurs the principle of equality between the parties, they do not proceed under equal conditions. When equality is affected, the impact on the principle of weighting must also be questioned. In short, the inadequate execution of protection measures is not a guarantee of legal security.